Congenital cutaneous candidiasis: A rare and unpredictable disease - Sujit A Jagtap; Pallavi P Saple; Saleha B Dhaliat (Wolters Kluwer Medknow Publications, 2011)
Congenital cutaneous candidiasis (CCC) is an extremely rare disorder that presents within the first 6 days of life. The manifestations ranges from diffuse skin eruption without any systemic symptoms to respiratory distress, hepatosplenomegaly, sepsis, and death. We report a neonate who presented with generalized skin eruptions at birth, characterized by erythematous macules and papules. The eruption involved head, face, neck, trunk, and extremities. Candida albicans was demonstrated on direct KOH smear, skin biopsy. The disease implies a congenital intrauterine infection and is different from neonatal candidiasis, which manifests as thrush or diaper dermatitis. The infection is acquired from the maternal genital tract in an ascending fashion. Clinical features, direct smear examination of specimen, and appropriate cultures are useful in differentiating the lesions from other more common dermatoses of the neonatal period. Topical antifungal therapy is sufficient unless systemic candidiasis is present. Prognosis for congenital cutaneous candidiasis is good.